Pengaruh ROA, BOPO, NPL dan LDR terhadap Financial Distress Pada Perusahaan Sektor Perbankan Periode 2011 - 2018 - Sriyanto Sriyanto; Yumniati Agustina (ITB Ahmad Dahlan Jakarta, 2020)
The purpose of this study is to examine the effect of ROA, BOPO, NPL and LDR on financial distress partially and simultaneously. The research objects are four state-owned banks listed on the Indonesia Stock Exchange in the 2011-2018 period. This research was conducted by conducting a logistic regression statistical test with a significance of 0.05, using the Statistical Package for Social Sciences (SPSS) version 24. The results of Variables in the Equation concluded that BOPO, NPL and LDR variables had a significant influence on financial distress. BOPO with Sig.0,022 value, NPL with Sig.0,029 value, LDR with Sig.0,032 value. While the ROA variable has no significant effect on financial distress with a Sig.0,139 value. The results of the omnibus test concluded that there was a simultaneous influence on the SOE Bank's financial distress on the Indonesia Stock Exchange in 2011-2018 with a value of Sig.0,000. The Summary Model results with the Nagelkerke R Square value in this study were 0.734 or 73.4%. This shows that the variation of the proposed variable ROA, BOPO, NPL and LDR can explain the financial distress variable, the remaining 26.6% is explained by other factors not included in this model.